Dampak Keikutsertaan Program Kartu Prakerja terhadap Keputusan Menjadi Gig Worker dan Pendapatan Gig Worker di Indonesia - Wahyuni, Ribut Nurul Tri; Asy-Syifa, Adha (Jurnal Ketenagakerjaan, 2025)
The COVID-19 pandemic caused many individuals to lose their jobs and face economic uncertainty, prompting a shift toward more flexible work arrangements such as gig worker work—freelance jobs based on digital platforms without formal employment contracts. To address the employment impact, the government launched the Kartu Prakerja Program as an effort to enhance skills and support labor adaptation. This study aims to analyze the general characteristics of Kartu Prakerja recipients and examine its impact on individuals’ decisions to become gig workers, as well as its effect on their earnings. The data used in this study come from the August 2024 National Labor Force Survey (Sakernas) by BPS-Statistics Indonesia, employing the Propensity Score Matching (PSM) method to reduce potential estimation bias and the Tobit model to account for censored earnings data. The findings reveal that the Kartu Prakerja Program increases the likelihood of individuals becoming gig workers but reduces their earnings. These results suggest that, although the program effectively facilitates transitions into the digital sector, further evaluation is necessary to ensure its benefits are distributed more evenly, particularly in supporting skill development and earnings growth among gig workers.